The utility of fasting plasma glucose to identify impaired glucose metabolism in women with polycystic ovary syndrome - Vrbikova, Jana; Hill, Martin; Fanta, Michael (Gynecological endocrinology, 2014)
Abstract We evaluated the utility of impaired fasting plasma glucose as defined by ADA to identify women with polycystic ovary syndrome (PCOS) affected by impaired glucose metabolism (i.e. impaired fasting glucose, impaired glucose tolerance and diabetes mellitus). In 330 women with PCOS, according to ESHRE criteria, an oral glucose tolerance test was done. Impaired fasting glucose was present in 36 women (12%), impaired glucose tolerance in 29 women (8.8%) and diabetes mellitus in 10 women (3%), 4 of them have fasting glucose higher than 7 mmol/l. The combination of impaired fasting glucose and impaired glucose tolerance was seen in 5 women (1.5%). The sensitivity of impaired fasting glucose for the detection of impaired glucose tolerance was 24% and specificity 91.8%. When fasting glucose above 5.6 mmol/l was used as the screening criterion, 28/35 subjects (80%) would have been missed. We conclude that fasting plasma glucose is not sufficiently sensitive for the detection of impaired glucose tolerance and diabetes mellitus type 2 in women with PCOS. Chinese abstract 评价ADA（美国糖尿病协会）定义的空腹血糖受损检测多囊卵巢综合征女性糖代谢受损（例如空腹血糖受损、糖耐量异常以及糖尿病）的有效性。对ESHER（欧洲人类生殖与胚胎学会）标准诊断的330名多囊卵巢综合征患者实施口服糖耐量试验。36名女性（12%）表现空腹血糖受损，29名女性（8.8%）表现糖耐量异常，10名女性（3%）表现为糖尿病，其中4名女性空腹血糖大于7mmol/L。5名女性（1.5%）同时具有空腹血糖受损及糖耐量异常。空腹血糖受损检测出糖耐量异常的敏感度及特异度分别为24%、91.8%。如果以空腹血糖大于5.6mmol/L作为筛查标准，28/35（80%）的患者将会被漏诊。我们推断：空腹血糖检测多囊卵巢综合征女性糖耐量受损及2型糖尿病的敏感性不足。